Book Reviews. Issue 1 (1st January 2017) - Bouchard, Norma; Benini, Stefania; Carbone, Marco Benoît; Heim, Julia; Annovi, Gian Maria; Koven, Mikel J.; Leuzzi, Laura; Raizen, Karen; Fiumara, Francesco; Ciofalo, Giovanni; Rigoletto, Sergio
SCHOOLING IN MODERNITY. THE POLITICS OF SPONSORED FILMS IN POSTWAR ITALY, PAOLA BONIFAZIO (2014) Toronto: University of Toronto Press, 304 pp., ISBN: 9781442615984, p/bk, $34.95NEW VISIONS OF THE CHILD IN ITALIAN CINEMA, DANIELLE HIPKINS AND ROGER PITT (EDS) (2014) Bern: Peter Lang, 342 pp., ISBN: 9783034302692, p/bk, £40.00UNFINISHED BUSINESS. SCREENING THE ITALIAN MAFIA IN THE NEW MILLENNIUM, DANA RENGA (2014) Toronto, Buffalo and London: University of Toronto Press, 264 pp., ISBN: 9781442615588, p/bk, £19.75OSSERVATORIO TV, BARBARA MAIO (2014) Creative Commons Public License (http://www.osservatoriotv.it/Benvenuto.html), 228 pp.SGUARDO, CORPO, VIOLENZA. SADE E IL CINEMA, ALBERTO BRODESCO (2014) Milano-Udine: Mimesis, 366 pp., ISBN-13: 9788857523057, h/bk, €24SO DEADLY, SO PERVERSE: 50 YEARS OF ITALIAN GIALLO FILMS, VOLUME 1: 1963–1973, TROY HOWARTH (2014) Baltimore, MD: Midnight Marquee Press Inc., 233 pp., ISBN: 9781936168507, p/bk, $49.95STORIA DEI MEDIA DIGITALI: RIVOLUZIONI E CONTINUITÀ, GABRIELE BALBI AND PAOLO MAGAUDDA (2014) Rome-Bari: Editori Laterza, 182 pp., ISBN: 9788858116272, p/bk, €20FILM SOUND IN ITALY: LISTENING TO THE SCREEN, ANTONELLA C. SISTO (2014) New York: Palgrave Macmillan, 224 pp., ISBN: 9781137387707, h/bk, $95FINIRAI: I RETROSCENA DELLA RIFORMA E IL FUTURO DELLA TELEVISIONE, ROBERTO FAENZA (2015) N. P.: Privately published, 224 pp., ISBN: 9788891091321, e-book, €4.99, p/bk, €17PALINSESTO: STORIA E TECNICA DELLA PROGRAMMAZIONE TELEVISIVA, LUCA BARRA (2015) Roma-Bari: Laterza, 202 pp., ISBN: 9788858117316, p/bk, €20, 00CINEMA, GENDER, AND EVERYDAY SPACE: COMEDY, ITALIAN STYLE, NATALIE FULLWOOD (2015) Basingstoke: Palgrave Macmillan, 272 pp., ISBN: 9781137403568, h/c/e-book, $95.00